288 Genetic architecture of new breed formation. (7th December 2018) - Paim, T; Blackburn, H; Hay, E; Wilson, C; Thomas, M; Kuehn, L; Paiva, S; McManus, C
Abstract: New breeds can be developed by combining two or more breeds into a composite population, thereby capitalizing on complementarity and retained heterosis. Evaluation of breed formation across generations has not been performed at the molecular level; therefore, we used Brangus cattle (3/8 Brahman x 5/8 Angus) as a model to identify the dynamics of new breed formation across 10 generations. Genotypic data (777, 962 SNP) from 68 Brahman, 95 Angus and 59 Brangus prominent AI sires born from 1970 to 2010 were evaluated. Their pedigrees were used to calculate the number of complete Brangus generations using the OptiSel package in R 3.4.2. After standard SNP data filters and linkage disequilibrium pruning, 158, 264 SNP genotypes from 220 bulls were chosen. ADMIXTURE analyses were executed using autosomal markers by chromosome, setting K equal to two and three. Brangus animals had 70.4% of Angus composition in all autosomes versus the expected 62.5% (t-test, P < 0.001). When K = 3, the establishment of the Brangus cluster was observed across the genome with a proportional assignment > 0.5. The sex chromosomes deviated from the autosomal pattern. Chromosome X had a high Angus proportion (83%) conserved across generations and Brahman contributed only to 9% of the Y chromosome. Regression analyses of cluster formation among autosomes and across generations showed ( P < 0.001) that Angus (β = -0.07) and Brahman (β = -0.03) clusters decreased while Brangus cluster increased (β = 0.10, R 2 = 0.43). Regressions by each autosome followed a similar pattern. Formation of the Brangus cluster became stable after the 5 th generation. These results provide a view into the evolution of a new breed.